2013
DOI: 10.1111/apm.12111
|View full text |Cite
|
Sign up to set email alerts
|

Lower mannose-binding lectin contributes to deleterious H1N1 2009 infection in children

Abstract: Mannose-binding lectin (MBL) has broad range of activity against viruses through the mechanisms of neutralization, opsonization, and complement activation. Prior studies have demonstrated that MBL inactivated the season's influenza virus. Due to the fact that children have no neutralizing antibody against H1N1 2009 virus, innate immunity may be crucial in the defense against influenza. Therefore, we studied whether MBL levels played a role in H1N1 2009 infection in children. In a prospective survey, we reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…However, other studies in adults have not found MBL to be associated with risk for sepsis (3942) or have reported a more nuanced picture that includes a mixture of both pro-inflammatory and anti-infection effects which may be beneficial or detrimental in varying disease states. (33, 34, 43) Specifically in pediatrics, six studies have demonstrated an association between lower MBL levels, or low-MBL producing haplotypes, and increased severity of infection-related disease (4, 5, 15, 16, 4446) while five studies showed similar findings to ours with a lack of association (12, 4650) and two studies concluded a possible protective role for low-producing MBL genotypes or levels. (12, 51)…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…However, other studies in adults have not found MBL to be associated with risk for sepsis (3942) or have reported a more nuanced picture that includes a mixture of both pro-inflammatory and anti-infection effects which may be beneficial or detrimental in varying disease states. (33, 34, 43) Specifically in pediatrics, six studies have demonstrated an association between lower MBL levels, or low-MBL producing haplotypes, and increased severity of infection-related disease (4, 5, 15, 16, 4446) while five studies showed similar findings to ours with a lack of association (12, 4650) and two studies concluded a possible protective role for low-producing MBL genotypes or levels. (12, 51)…”
Section: Discussionsupporting
confidence: 69%
“…(4, 11, 12, 16, 19, 33–38) We did find that MBL levels were diluted in patients that received extremely high volumes of fluid in the first 24 hours; a common occurrence in patients with severe sepsis that could possibly confound the relationship between MBL levels and infection-related critical illness. MBL levels were strongly genetically influenced by the combination of high, intermediate and low producing haplotypes.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Serum levels of MBL in children were shown to be significantly higher than that in adults (4 ± 3.960 μg/mL and 2.207 ± 1.73 μg/mL, respectively) . The mean serum level of MBL in children is higher than the MIC 50 required to inhibit influenza A(H1N1)pdm09, while in adults, it is lower than the MIC50, which may explain the protective effect of MBL in children . There are very few reports about the effect of high doses of MBL on influenza A(H1N1)pdm09 infection in humans.…”
mentioning
confidence: 99%